Blockchain and NFTs in the Cultural Heritage Domain: A Review of Current Research Topics - Helena Stublić; Matea Bilogrivić; Goran Zlodi (Heritage, 2023)
In the last few years, blockchain technology and NFTs have been the subject of much research in different sectors ranging from informatics, to medicine, to economics. Although it is most often associated with cryptocurrencies, due to its features of immutability and durability, this technology has found its place in various fields, including GLAM institutions. This article will review the literature from 2017 to 2022 dealing with blockchain and NFTs in the heritage sector. Topics covered, proposed models, and projects will be highlighted. Archives are currently leading the research into the use of blockchain technology and have already developed models such as TrustChain. However, libraries, museums, and galleries are also beginning to show an interest in the new technology and its potential benefits. Therefore, we also approached the GLAM sector as a whole, to emphasize the importance of the joint development on the advancement of shared approaches and protocols in utilizing blockchain technology to enhance the trustworthy management and preservation of digital resources. This is particularly important because GLAM institutions care for a shared heritage and serve a common audience. In the second part of the article we will discuss the proposed uses of the technology and highlight still unexplored topics that should be elaborated in further research. The aim of this paper is to make a synthesis of previous research and bring the potential of blockchain technology and NFTs closer to experts in the heritage field, given that they are still quite unknown.